2003
DOI: 10.1258/095646203762869197
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections and sexual behaviour among commercial sex workers in a rural district of Malawi

Abstract: Summary:In Thyolo District, Malawi, a study was conducted among commercial sex workers (CSWs) attending mobile clinics in order to; determine the prevalence and pattern of sexually transmitted infections (STIs), describe sexual behaviour among those who have an STI and identify risk factors associated with`no condom use' .There were 1817 CSWs, of whom 448 (25%) had an STI. Of these, the commonest infections included 237 (53%) cases of abnormal vaginal discharge, 109 (24%) cases of pelvic in¯ammatory disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 10 publications
1
21
1
6
Order By: Relevance
“…Strong associations between substance use and sexual risk behaviours have been reported previously and include smoking, drinking, and drug use being associated with sexual risk behaviours in general (Duncan, Strycker, & Duncan, 1999; Jackson, Sweeting, & Haw, 2012; Tu, Lou, Gao, Li, & Zabin, 2012), early sexual debut (Lowry et al, 1994), and number of sexual partners (Lowry et al, 1994; Shrier, Emans, Woods, & DuRant, 1997). Binge drinking has been associated with a higher number of partners (Guo et al, 2002), while more generally alcohol consumption has been associated with sexual debut, multiple sexual partners, and unprotected sex, all of which lead to an increased risk of HIV infection (Ayisi et al, 2000; Bassett et al, 1996; Clift et al, 2003; Lewis et al, 2005; Mnyika, Klepp, Kvale, & Ole-King’Ori, 1997; Myer, Mathews, & Little, 2002; Somsé, Chapko, & Hawkins, 1993; Zachariah et al, 2003). The increased risk of HIV infection may be attributable to the social consequences of substance use, which facilitates unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…Strong associations between substance use and sexual risk behaviours have been reported previously and include smoking, drinking, and drug use being associated with sexual risk behaviours in general (Duncan, Strycker, & Duncan, 1999; Jackson, Sweeting, & Haw, 2012; Tu, Lou, Gao, Li, & Zabin, 2012), early sexual debut (Lowry et al, 1994), and number of sexual partners (Lowry et al, 1994; Shrier, Emans, Woods, & DuRant, 1997). Binge drinking has been associated with a higher number of partners (Guo et al, 2002), while more generally alcohol consumption has been associated with sexual debut, multiple sexual partners, and unprotected sex, all of which lead to an increased risk of HIV infection (Ayisi et al, 2000; Bassett et al, 1996; Clift et al, 2003; Lewis et al, 2005; Mnyika, Klepp, Kvale, & Ole-King’Ori, 1997; Myer, Mathews, & Little, 2002; Somsé, Chapko, & Hawkins, 1993; Zachariah et al, 2003). The increased risk of HIV infection may be attributable to the social consequences of substance use, which facilitates unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in consistent condom use with the number of sexual partners suggests that those with more clients are likely to perceive that they are at a high risk of getting HIV28 and that those with fewer clients might not correctly perceive their risk of getting HIV.…”
Section: Discussionmentioning
confidence: 99%
“…We examined the association between a parsimonious set of socioecological factors and hazardous alcohol use (AUDIT score of ≥ 7) in a series of multivariable models among FSW who reported current alcohol use within the past 90 days. Based on the literature, these socioecological factors included: living environment (private house, bar or bottle shop, guesthouse or hotel) (Mbonye et al, 2013), years in sex work (<2, ≥2 years) (Li, Li, & Stanton, 2010), weekly number of clients (<10, 10–19, 20–29, ≥30 clients) (Li, Li, & Stanton, 2010), client ever demanded not using a condom during sex (yes, no) (Li, Li, & Stanton, 2010), condom use with client in the past 7 days (inconsistent, consistent) (Chersich et al, 2014; Chersich et al, 2007; Li, Li, & Stanton, 2010; Zachariah et al, 2003), reported alcohol use at last sex with a client (yes, no) (Chersich et al, 2007; de Graaf, Vanwesenbeeck, van Zessen, Straver, & Visser, 1995; Li, Li, & Stanton, 2010; Wojcicki & Malala, 2001), self-reported known HIV status (Li, Li, & Stanton, 2010), and self-reported receipt of STI treatment in prior 12 months (Chersich et al, 2007; Zachariah et al, 2003). The question used to assess consistency of condom use was “How often did you use condoms during vaginal sex with a paying sexual client in the last 7 days?”.…”
Section: Methodsmentioning
confidence: 99%